ANALYSIS VIDEO BASED LEARNING DESIGN IN PRACTICE COURSE AT VOCATIONAL SCHOOL - Puspitasari, Feny; Pratama, Mulki Rezka Budi (Universitas Negeri Yogyakarta, 2024)
This study aims to design educational videos as video-based learning and determine the design that makes students more interested in paying attention to the distance learning process. If students want to pay attention to the material during the learning process, students will also get the maximum learning experience. The study was focused on the Department of Fashion at SMKN 1 Dawuan Subang to improve clarity. To obtain empirical data, this study used quantitative comparative with data collection using questionnaires with census sampling. The number of respondents is 22 students. The steps are input measurement design video with Bandicam and output measurement obtained from the evaluation results based on three elements for video design and implementation: cognitive load, student engagement, and active learning together. The data collection technique used a questionnaire. The results indicate that video-based learning using Bandicam was most effective in organizing tempo, but more attention must be paid to segmentation because the visualization video was formal and tended to be static. Further research should explore video-based learning using more engaging and dynamic applications like Prezi or similar tools.